2002
DOI: 10.1016/s0022-2836(02)00464-3
|View full text |Cite
|
Sign up to set email alerts
|

Additional Binding Sites for Anionic Phospholipids and Calcium Ions in the Crystal Structures of Complexes of the C2 Domain of Protein Kinase Cα

Abstract: The C2 domain of protein kinase Calpha (PKCalpha) corresponds to the regulatory sequence motif, found in a large variety of membrane trafficking and signal transduction proteins, that mediates the recruitment of proteins by phospholipid membranes. In the PKCalpha isoenzyme, the Ca2+-dependent binding to membranes is highly specific to 1,2-sn-phosphatidyl-l-serine. Intrinsic Ca2+ binding tends to be of low affinity and non-cooperative, while phospholipid membranes enhance the overall affinity of Ca2+ and conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
125
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 39 publications
(54 reference statements)
20
125
0
Order By: Relevance
“…Domain-containing the PKC␣ C2 Ca 2؉ -binding Loops and the ␤3-4 Hairpin A basic region formed by lysine residues in the ␤-hairpin formed by ␤ strands 3 and 4 has been postulated to coordinate PS or PIP 2 in the membrane (Ochoa et al, 2002;Corbalan-Garcia et al, 2003;Rodriguez-Alfaro et al, 2004;MarinVicente et al, 2005), and an electron paramagnetic resonance study has demonstrated that this ␤3-4 hairpin lies in close proximity to the membrane surface (Kohout et al, 2003). To investigate the contribution of the ␤3-4 hairpin to specific Figure 5.…”
Section: Intracellular Targeting and Lipid Binding Of A Hybrid C2mentioning
confidence: 99%
See 4 more Smart Citations
“…Domain-containing the PKC␣ C2 Ca 2؉ -binding Loops and the ␤3-4 Hairpin A basic region formed by lysine residues in the ␤-hairpin formed by ␤ strands 3 and 4 has been postulated to coordinate PS or PIP 2 in the membrane (Ochoa et al, 2002;Corbalan-Garcia et al, 2003;Rodriguez-Alfaro et al, 2004;MarinVicente et al, 2005), and an electron paramagnetic resonance study has demonstrated that this ␤3-4 hairpin lies in close proximity to the membrane surface (Kohout et al, 2003). To investigate the contribution of the ␤3-4 hairpin to specific Figure 5.…”
Section: Intracellular Targeting and Lipid Binding Of A Hybrid C2mentioning
confidence: 99%
“…Earlier studies have suggested that lysines 197 and 199 in the ␤3 strand and lysines 209 and 211 in the ␤4 strand of PKC␣C2 are important in Ca 2ϩ -independent, PIP 2 -dependent binding to vesicles, PSand PIP 2 -dependent regulation of PKC␣ activity in vitro, and membrane residence (Ochoa et al, 2002;Corbalan-Garcia et al, 2003;Rodriguez-Alfaro et al, 2004;Marin-Vicente et al, 2005). The hypothesis that these lysine residues are important in PIP 2 recognition predicts that mutations at these positions would weaken membrane-targeting specificity in vivo and lipid-binding affinity in vitro.…”
Section: Intracellular Targeting and Lipid Binding Of Mutant Pkc␣ C2 mentioning
confidence: 99%
See 3 more Smart Citations